Surgical treatment of the fistulizing Crohn's disease with anterior abdominal wall reconstruction (Clinical case) - Yu. Ye. Kitsenko; O. S. Shifrin; P. V. Tsarkov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of clinical case presentation. To discuss the consequences of erroneous management approach at suspicion for appendicular infiltrate, as well as options and difficulties of complicated Crohn’s disease treatment. Summary. Surgical treatment of fistulizing Crohn's disease with interorgan and external fistulas with development of pathological cavity having anterior abdominal wall opening is described. Past history of disease was five years. The patient underwent appendectomy in the presence of infiltrate with subsequent development of external intestinal fistula. Repeated surgery for fistula elimination was unsuccessful, however allowed to establish Crohn's disease diagnosis. Patient refused from surgical treatment, therefore despite the lack of permanent remission at infliximab treatment, therapy was maintained until patient developed anaphylactic reaction. As a result, ileocecal resection along with resection of ileum fragment and distal third of sigmoid colon, restoration of intestinal continuity, and resection of anterior abdominal wall with fistulous tract block and subsequent reconstruction were executed. The collagen allo-graft is applied to restore anterior abdominal wall defect. At continuation of biological therapy by adalimumab no data on disease relapse were received. Conclusion. The presence of infiltration in the right iliac area requires ruling out of the Crohn's disease diagnosis. At fistulizing form treatment should be provided at the specialized institutions. It is important to note that treatment efficacy at exclusively conservative management, including biological therapy is quite low. Biological therapy allows to suppress disease manifestations and facilitate conditions for subsequent surgical intervention.